Research Progress on Th17/Treg Cell Imbalance in Epileptic Seizures - Mu L; Rong Y; Xin YJ; Zhang H; Xu Z (Journal of Inflammation Research)
Liu Mu,1,2 Yan Rong,1– 3,* Yang Jia Xin,1,2,* Hong Zhang,1,2,* Zucai Xu1– 3 1Department of Neurology, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, 563003, People’s Republic of China; 2Key Laboratory of Brain Function and Brain Disease Prevention and Treatment of Guizhou Province, Zunyi, Guizhou, 563003, People’s Republic of China; 3Collaborative Innovation Center of Tissue Damage Repair and Regeneration Medicine, Zunyi, Guizhou, 563003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zucai Xu, Department of Neurology, The Affiliated Hospital of Zunyi Medical University, 149 Dalian Road, Zunyi, Guizhou, 563003, People’s Republic of China, Email docxzc@126.comAbstract: Epilepsy is associated with widespread neurological circumstances due to aberrant neuronal discharges in the brain, which have significant adverse effects on patient’s quality of life and increase their risk of death. Immune imbalance, particularly disruption of the Th17/Treg cell balance, has gained increasing attention in the pathophysiology of epilepsy as our understanding of neuroimmune interactions improves. This paper examines the potential therapeutic effects and thoroughly discusses the processes by which the Th17/Treg cell imbalance contributes to the development of epilepsy. The primary emphasis is on the mechanism by which this imbalance impairs blood–brain barrier integrity, neuroinflammation, and other elements. On the therapeutic front, targeting the Th17/Treg axis for immune regulation—through approaches such as ketogenic diets, nanomaterials, and gene editing—shows promising prospects for restoring immune balance. By furthering our knowledge of the connection between Th17/Treg cell imbalance and epilepsy etiology, this work offers a crucial theoretical foundation for creating innovative immunotherapy approaches.Keywords: epilepsy, Th17/Treg cell balance, neuroinflammation, immune regulation, neuroimmune regulation